Investor protection and the value of shares: evidence from statutory rules governing variations of shareholders' class rights in Russia - Alexander Muravyev (Institute for the Study of Labor (IZA), 2009)
This paper uses a quasi-experimental framework provided by recent changes in Russian corporate law to study the effect of investor protection on the value of shares. The legal change analyzed involves the empowerment of preferred (non-voting) shareholders to veto unfavorable changes in their class rights. Based on a novel hand-collected dataset of dual class stock companies in Russia and using the difference-in-difference estimator, the study finds a statistically and economically significant effect of improved protection of preferred shareholders on the value of their shares. The result is robust to several changes in the empirical specification.
Keywords: G30; G38; K22; 330; Investor protection; company law; dual class stock; class rights; Russia; Anlegerschutz; Aktienrecht; Wirkungsanalyse; Börsenkurs; Shareholder Value; Russland